The Effect of the Implementation of the Ubudiyah and Akhlakul Karimah Proficiency Standard Program (SKUA) on the Formation of Religious Values of MTsN 3 Pacitan Students - Luthfi Hardiana Saputri; Muhammad Rohmad Abdan; Fithri Hidayati (Yayasan Rahmat Islamiyah, 2026)
This study aims to prove empirically how the implementation of the SKUA Program is able to shape students' religious values through a systematic process of internalizing values. Using an explanatory quantitative approach, data were collected from 112 grade VII students at MTsN 3 Pacitan through stratified proportional random sampling techniques. Data analysis was carried out by simple linear regression to measure the extent to which the SKUA program has an effect in increasing the formation of students' religious values. The results of the study revealed that the implementation of the SKUA Program has a positive and significant impact on the formation of students' religious values in an integrated manner. The important findings of this research confirm that the strength of SKUA lies in the incorporation of the four main pillars of the Qur'an: Hadith, Fiqh, Moral Faith, and Dhikr and Daily Prayer into one consistent evaluation system. The implication of this research emphasizes that Islamic education in madrassas will achieve optimal success if it is able to ensure that religious values are not only remembered intellectually, but are formed and practiced functionally in daily life.